2011
DOI: 10.2967/jnumed.110.084046
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Expression of Cyclooxygenase-1 in Activated Microglia and Macrophages During Neuroinflammation Visualized by PET with 11C-Ketoprofen Methyl Ester

Abstract: Cyclooxygenase (COX)-1 and -2 are prostanoid-synthesizing enzymes that play important roles in the regulation of neuroinflammation and in the development of neurodegenerative disorders. However, the specific functions of these isoforms are still unclear. We recently developed 11 C-labeled ketoprofen methyl ester as a PET probe that targets the COXs for imaging neuroinflammation, though its responsible isoform is yet to be determined. In the present study, we performed ex vivo and in vivo imaging studies with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 38 publications
3
57
0
Order By: Relevance
“…Importantly, expression of COX-1 was observed in activated microglia, which were tightly surrounded and enclosed by amyloid plaques. We previously reported that the expression level of COX-1 was constitutive and was not changed even in the lipopolysaccharideinduced inflamed area of the brain with activated microglia (8). Considering these results from our study, (S)-11 C-KTP-Me could detect the increased numbers of activated microglia that is closely associated with development of Ab plaques in AD progression.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Importantly, expression of COX-1 was observed in activated microglia, which were tightly surrounded and enclosed by amyloid plaques. We previously reported that the expression level of COX-1 was constitutive and was not changed even in the lipopolysaccharideinduced inflamed area of the brain with activated microglia (8). Considering these results from our study, (S)-11 C-KTP-Me could detect the increased numbers of activated microglia that is closely associated with development of Ab plaques in AD progression.…”
Section: Discussionsupporting
confidence: 72%
“…11 C-KTP-Me is promptly and almost completely hydrolyzed to acid form, 11 C-KTP, in rat brain within 5 min after the intravenous injection and can be used with PET to visualize time-dependent changes in COX-1 in activated microglia during neuroinflammatory processes (7,8). This finding provided evidence that COX-1 plays a critical role in microglial activation during acute neuroinflammation in vivo.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…There exist two genetically distinct isoforms of the cyclooxygenases: COX1 and COX2. COX1 is in general a constitutive enzyme, but has been demonstrated to be upregulated during certain inflammatory conditions (Schwab et al, 2000;Shukuri et al, 2011;Anrather et al, 2011;Matousek et al, 2010). The COX2 gene on the other hand has several transcriptional regulatory sites in its promoter and can be induced by various pro-inflammatory cytokines.…”
Section: Prostaglandin E2 Synthesis and Receptorsmentioning
confidence: 99%
“…A metabolite analysis in the rat brain revealed that the intravenously administrated methyl ester was initially taken up in the brain and then underwent hydrolysis to form a pharmacologically active form of the corresponding acids. Hence, we succeeded in the general 11 C-labeling of 2-arenylpropionic acids and their methyl esters as PET probes of NSAIDs to construct a potentially useful PET-probe library for the in vivo imaging of inflammation involved in the COX expression (Shukuri et al, 2011). The above racemic NSADs are readily separated by a chiral column to give an optically pure compound.…”
Section: Another Rapid Coupling Between Sp 3 -Sp 3 Hybridized Carbonsmentioning
confidence: 99%